2020
DOI: 10.18632/oncotarget.27637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the RUNX1-CBFβ transcription factor complex compromises mammary epithelial cell identity: a phenotype potentially stabilized by mitotic gene bookmarking

Abstract: RUNX1 has recently been shown to play an important role in determination of mammary epithelial cell identity. However, mechanisms by which loss of the RUNX1 transcription factor in mammary epithelial cells leads to epithelial-to-mesenchymal transition (EMT) are not known. Here, we report that interaction between RUNX1 and its heterodimeric partner CBFβ is essential for sustaining mammary epithelial cell identity. Disruption of RUNX1-CBFβ interaction, DNA binding, and association with mitotic chromosomes alters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…For instance, disruption of the RUNX1 interaction during mitosis leads to epithelial-to-mesenchymal transition. 64 Pharmacological inhibition of RUNX1 with Ro5-3335 normalized the altered inflammatory gene expression associated with in vitro hyperglycemia-induced trained immunity. The targeted intervention against RUNX1 provides further evidence of the involvement of RUNX1 in the downstream effects of hyperglycemia-induced trained immunity in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, disruption of the RUNX1 interaction during mitosis leads to epithelial-to-mesenchymal transition. 64 Pharmacological inhibition of RUNX1 with Ro5-3335 normalized the altered inflammatory gene expression associated with in vitro hyperglycemia-induced trained immunity. The targeted intervention against RUNX1 provides further evidence of the involvement of RUNX1 in the downstream effects of hyperglycemia-induced trained immunity in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a role for CBFB in the suppression of breast cancer has recently emerged, and it has been reported that nuclear CBFB/RUNX1 complex represses the oncogenic NOTCH signaling pathway in breast cancer [ 98 ]. Moreover, an efficient function of the CBFB/RUNX1 complex is necessary for the maintenance of the normal mammary epithelial phenotype [ 99 ]. In particular, the CBFB/RUNX1 complex represses NOTCH3 [ 98 ], and this observation establishes another interesting link among the underexpression of a 16q gene (CBFB)—the overexpression of 1q-located gamma-secretase component and the pathway “NOTCH3 Activation and Transmission of Signal to the Nucleus,” as described in previous paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…The H3K4ac responsive gene promoter regions not bound by ERα (clusters 1 and 2) correspond to genes associated with cell cycle regulation, DNA metabolic processes and mitotic checkpoints ( Fig 4E ; TSS). Genes that annotate to enhancer regions (cluster 3) are enriched with signaling pathways of validated estrogen networks and include several estrogen-related pathways in addition to transcriptional regulation by RUNX1, a pathway linked to breast cancer and tumor suppression [ 47 51 ]. Of significance, a role for RUNX1 in mediating ERα tethering versus direct genomic recruitment to estrogen response elements has been reported [ 52 ].…”
Section: Resultsmentioning
confidence: 99%